The World Bank scales up insights from Climate-Smart Villages in Niger - CGIAR Research Program on Climate Change, Agriculture and Food Security; World Agroforestry Centre (2016)
Niger’s population is highly dependent on agriculture but faces constant risks aggravated by climate change. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) West Africa Program set up the Kampa Zarma Climate-Smart Village (CSV) in Niger to test climate-smart agriculture (CSA) interventions. To engage the local community, these interventions were designed through a participatory diagnosis. CCAFS and World Agroforestry Centre (ICRAF) have documented the implications and successes of various CSA practices. These experiences were used by the World Bank to inform the design of its 7-year USD 111 million CSA project in Niger, aligned with the large government initiative ‘Nigeriens Nourish Nigeriens’.